40 Begriffe für eine Schreibwissenschaft. Konzeptuelle Perspektiven auf Praxis und Praktiken des Schreibens

Effects of task difficulty on visual processing speed - Banh, Ngoc Chi; Scharlau, Ingrid

Measuring Visual Attention Capacity Across xReality - Biermeier, Kai; Scharlau, Ingrid; Yigitbas, Enes (Proceedings of the 17th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2024))

The Importance of Distrust in AI - Peters, Tobias Martin; Visser, Roel W. (Communications in Computer and Information Science)

Wissenschaft und Alltagserfahrung: Überlegungen zur Wissenschaftsdidaktik der Psychologie - Scharlau, Ingrid (Wissenschaftsdidaktik II: Einzelne Disziplinen)
Keywords: Unterrichtsfach Psychologie

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

Schreibfokussierte Graduiertenförderung: Reflexive Spezialisierung für interdisziplinäre Forschungskontexte - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre)

Turning Disciplinary Differences from a Brake into a Motor in Higher Education (Collaboration) - Sloane, Hannah Sabrina; Schmöckel, Sabrina

First steps towards real-time assessment of attentional weights and capacity according to TVA - Banh, Ngoc Chi; Scharlau, Ingrid (Abstracts of the 65th TeaP)

Transitivitätscharakteristika als Werkzeug in der systematischen qualitativen Metaphernanalyse - Karsten, Andrea; Schwede, Jana; Körber, Miriam; Scharlau, Ingrid (Die Praxis der systematischen Metaphernanalyse)